Peran Wanita dan Relasi Gender dalam Keluarga Buruh Tani Wanita di Regu Tanam Mulyo Asri Desa Pontang Kecamatan Ambulu Kabupaten Jember - Aulia Syifa Abdillah; Diah Puspaningrum (Fakultas Pertanian Universitas Jember, 2021)
This study aims to determine gender roles and gender relations in the family of female farm workers in the Mulyo Asri women's planting team in Pontang Village, Ambulu Sub-district, Jember District. The theory used in the research uses the theory of Gender. This study used a qualitative approach, with the method of determining informants using purposive sampling technique. Data collection techniques in this study by means of in-depth interviews, observation, and documentation study. Methods of data analysis in this study using the analysis method of Harvard and Miles and Huberman. The data validity test used technical triangulation and source triangulation testing techniques. The results of this study are the division of labor in the family of female farm workers, which includes productive activities, reproductive activities, and social activities. From an emic perspective, the participation of a wife in work is something that is normal and often happens. From an ethical perspective, there is a gender issue, namely the existence of a heavier workload experienced by the wife. The relationship that exists in the family of female farm workers is in the form of access to control over resources and benefits carried out by the family of female farm workers in Pontang Village, Ambulu Sub-district, Jember District. Keywords: Gender Roles, Gender Relations, Farm Workers, Family